1974
DOI: 10.1042/bj1420027
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of l-asparagine synthetase in the principal organs of several mammalian and avian species

Abstract: A survey was conducted of the distribution of l-asparagine synthetase and of l-asparaginase in the principal organs of representative mammals and birds. Although a radiometric assay was used as a routine, several additional criteria, including enzymic and chromatographic ones, were used to verify that the product of the synthetase was l-asparagine. Recoveries of exogenous l-asparagine were assessed in the presence of a number of mouse organs and found to be about 85%. In addition, evidence is presented for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…This was not true of added Asp under similar conditions (55) because of its impermeability into periportal hepatocytes (57). A survey of various mammalian and avian species has shown that human and mouse liver have comparable asparagine synthetase activities but that mouse liver has a thousandfold increased activity of asparaginase compared with that of human (58). An increased Asn synthesis through the increased expression of the Asns gene in the Ctrn-KO and the double knock-out mice therefore could supply Asn as a diffusible source of cytosolic Asp within the mouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…This was not true of added Asp under similar conditions (55) because of its impermeability into periportal hepatocytes (57). A survey of various mammalian and avian species has shown that human and mouse liver have comparable asparagine synthetase activities but that mouse liver has a thousandfold increased activity of asparaginase compared with that of human (58). An increased Asn synthesis through the increased expression of the Asns gene in the Ctrn-KO and the double knock-out mice therefore could supply Asn as a diffusible source of cytosolic Asp within the mouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…ASNS is expressed to varying degrees within human organs (http://www.proteinatlas.org/ENSG00000070669-ASNS/tissue), 5 but is particularly high in pancreas (32). However, when considering the requirement for asparagine at the level of individual cells, ASNS deficiency leads to extracellular asparagine dependence, as discussed above for ALL cells.…”
Section: Asparagine Synthetase Deficiencymentioning
confidence: 98%
“…Unfortunately, mice, unlike humans, express endogenous L-ASP (at high levels; ref. 48), so they are questionable as models for assessment of ASNS as a biomarker for asparagine depletion therapy.…”
Section: Discussionmentioning
confidence: 99%